2014
DOI: 10.1007/s00383-014-3625-4
|View full text |Cite
|
Sign up to set email alerts
|

Does pneumoperitoneum adversely affect growth, development and liver function in biliary atresia patients after laparoscopic portoenterostomy?

Abstract: PP during LPE would appear to have no adverse effects on overall growth/development and liver function in BA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Twenty-nine studies (1 RCT and 28 NRSs) dealt with four types of procedures, such as Kasai's portoenterostomy (1 RCT 191 and 13 NRSs 192 193 194 195 196 197 198 199 200 201 202 203 204 ), choledochal cyst resection (11 NRSs 192 205 206 207 208 209 210 211 212 213 214 ), cholecystectomy (3 NRSs 215 216 217 ), and hydatid liver cyst resection (1 NRS 218 ). The results are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies (1 RCT and 28 NRSs) dealt with four types of procedures, such as Kasai's portoenterostomy (1 RCT 191 and 13 NRSs 192 193 194 195 196 197 198 199 200 201 202 203 204 ), choledochal cyst resection (11 NRSs 192 205 206 207 208 209 210 211 212 213 214 ), cholecystectomy (3 NRSs 215 216 217 ), and hydatid liver cyst resection (1 NRS 218 ). The results are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found this better in terms of less tissue injury, no mobilization of the liver, small wounds etc. 32,33 On the other hand, some studies discourage the use of LPE as a method of BA management. 30,31 It was found that the risk factors played a significant role to attain a successful outcome in the treatment of BA.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 However, after the recent advancement of the technology and instrumentation, some researchers reported the good outcome of the LPE. 32,33 In addition, there are many advantages of LPE including less tissue injury, no mobilization of the liver, smaller wounds, decreased pain and fewer abdominal adhesions. 28 In the meta-analysis published by Li et al in 2019, the outcome of the two techniques (OPE and LPE) for the management of BA patients was compared.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Furthermore, prolonged pneumoperitoneum was another concern within the learning curve, which may compromise liver function (11)(12)(13). Nakamura et al (14), however, proposed that prolonged pneumoperitoneum during LKPE may have no adverse effects on overall growth or development and liver function in patients with BA. In our study, the median operative time of LKPE was 263 minutes, which was much longer than 188 minutes of OKPE (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%